Yoga for Dementia Care: A Review - Amitava Acharyya (Preventive Medicine: Research & Reviews, 2024)
This review examines the potential of yoga as a non-pharmacological intervention for the care and control of a person with dementia. Six research articles were retrieved from Medline databases (search conducted on March, 2022) using the terms ‘Yoga’ and ‘Dementia’/‘Alzheimer’s’/‘Mild Cognitive Impairment’. The review identified is limited to moderate evidence for yoga’s effectiveness in improving cognitive activities, memory capacity, quality of life and daily living activities in individuals with dementia. Further high-quality further robust and rigorous research is warranted to draw definitive conclusions about yoga’s role in dementia care.